Cytotoxic CD4+ T cells are correlated with better prognosis in Han Chinese grade II and grade III glioma subjects and are suppressed by PD-1 signaling. (4th May 2017) - Ge, Jing; Zhao, Lina; Li, Guanggang; White, Jason; Song, Zongchang; Wang, Zhifei; Zhao, Ludong
Abstract : Purpose : Malignant gliomas are the most common tumors in the central nervous system with a poor prognosis. Recently, CD4 + cytotoxic T cells (CTLs) are being increasingly recognized as possessing antitumor capacity. However, their presence, activity and regulation in glioma have not been investigated in detail. Methods : To examine this, 72 grade II and grade III Han Chinese glioma patients and 30 Han Chinese healthy controls were investigated. Results : We found that compared to healthy controls, glioma patients had significantly upregulated frequencies of circulating CD4 + CTLs, identified by the expression of granzyme A (GzmA), granzyme B (GzmB) and/or perforin. The stimulated CD4 + CTLs in grade II and grade III glioma patients also had less proliferative ability than those in healthy controls, a feature of suppression that progressed with tumor grade. The frequencies of GzmB-expressing circulating CD4 + CTLs were directly associated with prognosis. We hypothesized that the programed death 1 (PD-1)/PD-ligand 1 (L1) interaction possibly contributed to the suppression of CD4 + CTLs in grade II and grade III glioma, since an upregulation of PD-1 was observed on CD4 + CTLs in glioma compared to those in the healthy individuals. Blockade of the PD-1/PD-L1 interaction with neutralizing antibodies significantly increased the proliferation and granzyme or perforin production by CD4 + CTLs in grade II and grade III glioma patients. Conclusions : These data suggest that the CD4 + CTLs in grade II and grade III glioma patients contribute to antitumor immunity and could be suppressed by PD-1 signal transduction.